A socialist history of the French revolution - Jaurès, Jean, 1859-1914 (Pluto Press, 2015)
"Jean Jaurès was the celebrated French Socialist Party leader, assassinated at the outbreak of the First World War in 1914. Published just a few years before his death, his magisterial A Socialist History of the French Revolution, has endured for over a century as one of the most influential accounts of the French Revolution ever to be published. Mitchell Abidor's long-overdue translation and abridgement of Jaurès's original six volumes brings this exceptional work to an Anglophone audience for the first time. Written in the midst of his activities as leader of the Socialist Party and editor of its newspaper, L'Humanitè, Jaurès intended the book to serve as both a guide and an inspiration to political activity, which is just as relevant today."--Publisher's description.